Living Wonders in Mathematics - Subedi, Shantiram (Damak Campus Journal, 2025)
Mathematics is often seen as a rigid, logical displine, but beneath its structured surface lie astonishing patterns, paradoxical truth, wonderful logical consequences, and applications that shape our world. This paper highlights some of the captivating Wonders of Mathematics and then explores indepth their intutive mathematical aspects from timelss theorems, facts to modern breakthoughts revealing why mathematics remains one of the humanityʻs most imaginative and poweerful tools. This paper presents materials that evoke the wonders on mathematics in an accessible style its primary goal.